O014 Podoplanin (GP38), a marker of synovial inflammation, is an excellent therapeutic target in mouse collagen-induced arthritis. (21st February 2018) - Desanti, GE; Saghir, AN; Naylor, AJ; Kemble, S; Falconer, J; Wehmeyer, C; Marshall, JL; Nakamura, K; Goodall, M; Navarro-Núñez, L; Watson, SP; Buckley, CD
Abstract : Introduction: In patients with rheumatoid arthritis, synovial fibroblasts (SF) highly up-express the surface protein Podoplanin (PDPN) while its ligand, CLEC-2, is brought into the synovial membrane by platelets. 1, 2 PDPN is also up-expressed by synovial Th17 T cells from arthritic mice. 3, 4 Interestingly, IL-17 secretion by human Th17 T cells is triggered by direct cellular contacts with SF in a PDPN-dependent manner in vitro. 5 PDPN is then an excellent biomarker and a potential regulator of joint inflammation. Despite these observations, in vivo experimental approaches that explore the therapeutic opportunity of targeting PDPN during the disease are missing. Objectives: We aimed at refining the understanding of PDPN expression patterns inside the mouse synovium. We explored the therapeutic benefits from an anti-PDPN antibody in mice with auto-immune arthritis. Methods: PDPN expression patterns were investigated from freshly isolated TNFa-overexpressing mouse synoviocytes by histology and FACS. The functions of PDPN expressing synoviocytes were sought by cell sorting and quantitative PCR analysis. An anti-PDPN antibody was administrated to collagen-induced arthritis (CIA) mice from day 26 post-immunisation. The CIA mice disease activity was monitored daily until day 42 and their tissues (plasma, synovium, bones, lymph nodes) analysed by ELISA, FACS, histology, micro-CT, T cell in vitro stimulation and multiplex cytokine assays. Results: Joint inflammation triggered PDPN up-expression on a pro-inflammatory SF subset with concurrent accumulation of PDPN +anti inflammatory macrophages. These populations disappeared with the resolution of inflammation. Anti-PDPN treated CIA mice were efficiently protected from arthritis as demonstrated by their clinical features, their reduced leucocyte and non-haematopoietic cell accumulations into the joints as well as their attenuated bone erosion and remodelling. The T cell cytokine expression profile was normal in these mice. The anti-collagen auto-antibody plasma titres were significantly reduced in the anti-PDPN treated CIA mice compare to the control group. Conclusions: We demonstrated for the first time that PDPN is expressed by pro-inflammatory and anti-inflammatory cell subsets during joint inflammation. Moreover, we are providing strong evidences that an anti-PDPN antibody restrains auto-immune arthritis in mice. This therapeutic benefit provided by the anti-PDPN antibody correlates with a reduction of circulating auto-antibody titres. This observation suggests that the anti-PDPN antibody might interfere with the micro-environment supporting B cell activation and/or plasma cell survival. References: . Ekwall AK, et al. Arthritis Res. Ther2011;13:R40. . Del Rey MJ, et al. PLoS One2014;9:e0099607. . Miyamoto Y, et al. Molecular Immunology2013;54:199. . Jones GW, et al . J. Exp. Med 2015;212:1793. . Noack M, et al. Arthritis Res. Ther2016;18:148. Disclosure of interest: None declared